1976
DOI: 10.1111/j.1432-1033.1976.tb09993.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal DNA-Dependent RNA Polymerases. Purification and Molecular Structure of Hen-Oviduct and Liver Class-B RNA Polymerases

Abstract: Hen oviduct and liver class B RNA polymerases have been extensively purified and their molecular structure has been analysed. While only one enzyme B form (BIIb) was found in liver, three forms (BI, BIIa and BIIb) were resolved from oviduct. The molecular structures of the various class B RNA polymerase forms purified from hen oviduct and liver are identical to the corresponding forms previously purified from calf thymus and rat liver. At the present level of resolution the only difference lies in a slight dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recently, Krebs and Chambon found a unique form of enzyme B in hen liver (BIIb) and three forms in the oviduct (BI, BIIa, and BIIb) [51]. Copurification of liver and oviduct enzymes excluded the presence of a specific protease activity in liver nuclei [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Krebs and Chambon found a unique form of enzyme B in hen liver (BIIb) and three forms in the oviduct (BI, BIIa, and BIIb) [51]. Copurification of liver and oviduct enzymes excluded the presence of a specific protease activity in liver nuclei [51].…”
Section: Discussionmentioning
confidence: 99%
“…Copurification of liver and oviduct enzymes excluded the presence of a specific protease activity in liver nuclei [51]. Therefore, if there was a limited proteolysis of liver enzymes, it could only take place during the preparation of nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Samples (0.3 mL) of wheat germ RNA polymerase II (specific activity, 180 units/mg) and calf thymus RNA polymerase II (specific activity, 104 units/mg) in buffer D, but with 12.5% glycerol, containing 100 mM ammonium sulfate were each layered onto 4.6-mL linear 17.5-35% glycerol gradients in 0.05 M Tris-HCl (pH 7.9)-0.1 mM Na2EDTA-0.5 mM dithiothreitol-100 mM ammonium sulfate-0.2% Nonidet-P-40 detergent. The gradients were centrifuged for 8 h in a Spinco SW 65 rotor at 0 °C as described by Krebs and Chambon (1976). Thirteen drop fractions were collected from the bottom of the tube (19-21 fractions/gradient) and assayed immediately.…”
mentioning
confidence: 99%
“…5). Figure 5 also showed that the faintly staining high mol wt polypeptides discussed above in Figure 2 (17), rat livers (15), and mouse plasmacytoma (24) all resolve into three components in nondenaturing gels. RNAP II purified from animal tissues exhibits various patterns in nondenaturing gels which were not generally correlated with physiological transitions.…”
Section: Resultsmentioning
confidence: 94%